An improvement in the reconstruction of digestive tract after total gastrectomy: ultra-short cecum - Ding, Shikang; Yang, Xin; Li, Yibo; Zheng, Xiaohao; Song, Yanyang; Xie, Yibin (Frontiers in Oncology, 2023)
This study aimed to evaluate the utility and complications of ultra-short cecum (USC) in the reconstruction of digestive tract after total gastrectomy (TG) for the alleviation of reflux esophagitis and to determine its effect on long-term nutritional status.Patients who underwent TG with USC or normal cecum (NC) at a single institution between June 2018 and December 2020 were included in this study. The inclusion and exclusion criteria were defined, and the primary endpoints were reflux esophagitis, anastomotic leakage and postoperative nutritional status. The long-term nutritional status was evaluated by the change trend of laboratory blood tests, including total protein, prealbumin, hemoglobin, and total leukocytes.Totally 240 cases were included in the final analysis out of 496 patients who received TG with USC or NC. Postoperative reflux esophagitis was significantly higher in the NC group than in the USC group (24.7% versus 7.7%, P = 0.001), and the NC group had a higher incidence of severe esophagitis symptoms compared to the USC group (13.6% versus 0.00%, P < 0.001), and the incidence of anastomotic leakage in the USC group was similar to that in the NC group (9.0% versus 6.2%, P = 0.6). There was no significant difference in long-term nutritional status between the USC and NC groups in the two years following the surgery (P > 0.05).Ultra-short cecum after total gastrectomy should be more actively recommended due to its significant reduction in reflux esophagitis and similar incidence of anastomotic leakage and nutritional status compared with normal cecum after total gastrectomy.